The Capacity Gain of Orbital Angular Momentum Based Multiple-Input-Multiple-Output System - Zhang, Zhuofan; Zheng, Shilie; Chen, Yiling; Jin, Xiaofeng; Chi, Hao; Zhang, Xianmin (Scientific reports, 2016)
Wireless communication using electromagnetic wave carrying orbital angular momentum (OAM) has attracted increasing interest in recent years and its potential to increase channel capacity has been explored widely. In this paper, we compare the technique of using uniform linear array consist of circular traveling-wave OAM antennas for multiplexing with the conventional multiple-in-multiple-out (MIMO) communication method and numerical results show that the OAM based MIMO system can increase channel capacity while communication distance is long enough. An equivalent model is proposed to illustrate that the OAM multiplexing system is equivalent to a conventional MIMO system with a larger element spacing, which means OAM waves could decrease the spatial correlation of MIMO channel. In addition, the effects of some system parameters, such as OAM state interval and element spacing, on the capacity advantage of OAM based MIMO are also investigated. Our results reveal that OAM waves are complementary with MIMO method. OAM waves multiplexing is suitable for long-distance line-of-sight (LoS) communications or communications in open area where the multi-path effect is weak and can be used in massive MIMO systems as well.